SUDEP in patients with epilepsy and nonepileptic seizures. Issue 3 (6th June 2019) - Verducci, Chloe; Friedman, Daniel; Devinsky, Orrin
Abstract: We report 13 SUDEP cases in the North American SUDEP Registry with both psychogenic nonepileptic seizures (PNES) and epileptic seizures (ES) among a consecutive series of 231 cases (excluding epileptic encephalopathies). On average, cases of PNES + ES died at a younger age (23 ± 11 years) than the ES‐only cohort (30 ± 14 years), and died an average of 3 years after PNES diagnosis. We found no statistically significant confounding cardiac, respiratory, or psychiatric comorbidities and equal rates of anti‐seizure medication adherence, although there was a trend for higher rates of psychiatric disorders in the PNES group. Our findings confirm that patients with comorbid ES and PNES can die from SUDEP and that there may be a high‐risk period after the diagnosis of PNES is made in patients with comorbid ES. Such patients should be closely monitored and provided with coordinated care of both their epilepsy and psychiatric disorder(s).